Obtaining Glenoid Positioning Data from Scapular Palpable Points In Vitro - Jordan H. Trafimow; Alexander S. Aruin (Advances in Orthopedics)
Both clinical and biomechanical problems affecting the shoulder joint suggest that investigators should study force transmission into and out from the scapula. To analyze force transmission between the humeral head and the glenoid, one must know the position of the glenoid. Studies have analyzed the position of the scapula from the positions of three palpable points, but the position of the glenoid relative to three palpable points has not been studied. Dry scapulae () were subjected to X-rays and a critical angle, (which relates the plane determined by the three palpable points on the scapula to a plane containing the glenoid center and the first two palpable points) was calculated. The mean value for was degrees. The obtained allows us to determine the position of the glenoid from three palpable points. This information could be used in calculation of forces across the shoulder joint, which in turn would allow optimizing the choice of strengthening exercises.